Plasma concentrations of BDNF and IGF-1 in abstinent cocaine users with high prevalence of substance use disorders: relationship to psychiatric comorbidity. - María Pedraz; Ana Isabel Martín-Velasco; Nuria García-Marchena; Pedro Araos; Antonia Serrano; Pablo Romero-Sanchiz; Juan Suárez; Estela Castilla-Ortega; Vicente Barrios; Rafael Campos-Cloute; Juan Jesús Ruiz; Marta Torrens; et al. (PLoS ONE)
Recent studies have identified biomarkers related to the severity and pathogenesis of cocaine addiction and common comorbid psychiatric disorders. Monitoring these plasma mediators may improve the stratification of cocaine users seeking treatment. Because the neurotrophic factors are involved in neural plasticity, neurogenesis and neuronal survival, we have determined plasma concentrations of brain-derived neurotrophic factor (BDNF), insulin-like growth factor 1 (IGF-1) and IGF-1 binding protein 3 (IGFBP-3) in a cross-sectional study with abstinent cocaine users who sought outpatient treatment for cocaine (n = 100) and age/body mass matched controls (n = 85). Participants were assessed with the diagnostic interview 'Psychiatric Research Interview for Substance and Mental Disorders'. Plasma concentrations of these peptides were not different in cocaine users and controls. They were not associated with length of abstinence, duration of cocaine use or cocaine symptom severity. The pathological use of cocaine did not influence the association of IGF-1 with age observed in healthy subjects, but the correlation between IGF-1 and IGFBP-3 was not significantly detected. Correlation analyses were performed between these peptides and other molecules sensitive to addiction: BDNF concentrations were not associated with inflammatory mediators, lipid derivatives or IGF-1 in cocaine users, but correlated with chemokines (fractalkine/CX3CL1 and SDF-1/CXCL12) and N-acyl-ethanolamines (N-palmitoyl-, N-oleoyl-, N-arachidonoyl-, N-linoleoyl- and N-dihomo-γ-linolenoyl-ethanolamine) in controls; IGF-1 concentrations only showed association with IGFBP-3 concentrations in controls; and IGFBP-3 was only correlated with N-stearoyl-ethanolamine concentrations in cocaine users. Multiple substance use disorders and life-time comorbid psychopathologies were common in abstinent cocaine users. Interestingly, plasma BDNF concentrations were exclusively found to be decreased in users diagnosed with both primary and cocaine-induced disorders for mood and anxiety disorders. In summary, BDNF, IGF-1 and IGFBP-3 were not affected by a history of pathological use of cocaine supported by the absence of associations with other molecules sensitive to cocaine addiction. However, BDNF was affected by comorbid mood disorders. Further research is necessary to elucidate the role of BDNF and IGF-1 in the transition to cocaine addiction and associated psychiatric comorbidity.